Persepsi Masyarakat Terhadap Keberadaan Rumah Potong Ayam (RPA) di Kelurahan Kaligandu Kecamatan Serang Kota Serang Banten - Lazuardi, Muhammad Abrori; Herlina, Linda; Firman, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This research was conducted in Pejaten Neighborhood, Kaligandu Village, Serang District, Serang City, Banten during October 2024 by considering that the Chicken Slaughterhouse is in the middle of the community with the aim of examining the perceptions of the community around the chicken slaughterhouse on its positive and negative impacts. This research used survey method (observation and interview) with descriptive statistical data analysis using likert scale. The results showed that the community had a positive perception of the traces of the presence of chicken slaughterhouses with a total score of 409 which was included in the useful category. But on the other hand, the negative impact indicator shows a quite disturbance category with a score of 271. Overall, although there are benefits, the negative impacts also need to be considered from the presence of abattoirs around the community.